Penciptaan Teater Tubuh - Tony Supartono (LP2M ISBI Bandung, 2016)
ABSTRACTÂ The Â process Â of creative Â of theatricalÂ Â body is an offer of renewal Â theatre Â by exploring and processing Â the body, which become the main Â key in theatre production.Â Â This paper proposed the design to offer new thinking, Â and alternative Â thinking.Creative Â of theatrical Â bodyis a process Â of body practice Â with the body consciousness Â either Â as an idea or the body itself Â as the idea, the learning Â process of the body until get the consciousness Â movements which resulted by the body. For Â the process of practice Â the researcher Â called it as â€œActorÂ Body Interrogationâ€ Â that is the process of breaking Â and re-asking Â the problem of actorsâ€™ Â body.Creative Â of theatrical Â body offers new point Â of view about Â the body, which not only as the expression media, but the body itself stands Â alone as its identity. The body is considered Â as the phenomenaÂ Â which stand Â alone and also making relationship to the environment, Â spaces, build- ings, vehicles, peoples, even to the society Â and their Â ideology which dominant. Â Therefore, cre- a t i v e Â o f Â t h e a tr i ca l b o d y i s a p ro ce s s o f Â com p l e t e Â t h e a t re Â b e t we e n a ct o r, Â a n d Â t h e Â b o d y laugaugeinclude its relationship to the society.Â Keyword: Â theatre, Â body, body interogation,Â Â public Â spaceÂ Â Â Â Â ABSTRAKÂ Proses penciptaan teater tubuh merupakan penawaran pembaharuan teater dengan menggarap dan mengolah tubuh, yang menjadi kunci utama produksi teater. Paper ini mengajukan rancangan untuk menawarkan pikiran-pikiran baru, pikiran-pikiran alternatif. Penciptaan teater tubuh adalah proses latihan tubuh dengan kesadaran tubuh sebagai gagasan atau tubuh itu sendiri sebagai ide, proses belajar pada tubuh sehingga mendapat kesadaran gerak-gerak yang dilahirkan oleh tubuh. Proses latihannya penulis memberi nama â€œinterogasi tubuh aktor â€, yaitu proses membongkar dan mempertanyakan kembali persoalan tubuh aktor.Penciptaan teater tubuh menawarkan pandangan baru tentang tubuh yang bukan sekedar media ungkap tetapi tubuh itu sendiri mandiri sebagai sebuah identitas. Tubuh dipandang sebagai fenomena yang berdiri sendiri tetapi sekaligus melakukan relasi dengan lingkungan: jalan, bangunan, kendaraan, orang-orang dan bahkan seluruh masyarakat dan ideologinya yang sedang dominan. Dengan demikian penciptaan teater tubuh adalah proses teater yang utuh antara aktorÂ Â dan bahasatubuh sekaligus relasinya dengan masyarakat.Â Kata kunci : teater, tubuh, interogasi tubuh, ruang publik.